ANALISIS FAKTOR LINGKUNGAN FISIK RUMAH YANG MEMPENGARUHI KEJADIAN TUBERKULOSIS PARU DI WILAYAH KERJA PUSKESMAS BANYU URIP KABUPATEN PURWOREJO - -, Suherman; -, Cokroaminoto; Mardiati, Ike (LPPM STIKES MUHAMMADIYAH GOMBONG, 2014)
In Indonesia, tuberculosis is a major public health problem. In 2011, the number of tuberculosis patients in Indonesia is estimated at 429,000 people. Many factors can stimulate the occurrence of pulmonary TB, especially among the home environment had a major impact on the health status of residents, especially in the spread of tuberculosis germs The aim of this study is to Â know the physical environmental factors affecting the incidence of pulmonary tuberculosis in the work area Banyuurip Purworejo Health Center in 201 This study design is analytical survey method with cross-sectional. This research was conducted in the work area Puskesmas Banyuurip Purworejo in August-October 2012. Total sample of 72 people who suffer from cough > 2 weeks, taken using accidental sampling. Data is collected through interviews using questioner and observation conditions of a respondents house. Data were analyzed using chi-square and logistic regression to determine the dominant factors that influence the incidence of tuberculosis. The study shows that Â of 72 respondents 11 people suffering from BTA (+) and 61 people suffered BTA (-). From the results of Chi-Square test, room lighting factors influence the incidence of tuberculosis (p = 0.022), room humidity effect on the incidence of tuberculosis (p = 0.009), type of house floor had no effect on the incidence of tuberculosis (p = 0.669) and the effect on residential density incidence of tuberculosis (p = 0.036). From the analysis using logistic regression showed that the most influence factor is the room lighting (OR = 0.12). Keywords: environmental factors, lighting, humidity, occupancy density